Terapi Audio Murotal Al-Qur’an terhadap Kesehatan Mental - Nisa Zakiyah (Gunung Djati Conference Series, 2023)
Many people today use music as a medicine or therapy to relieve stress. The type of music used for self-therapy is classical music, but it is true that music can help relax the mind. This research study tries to explain it in Islamic psychotherapy, but in addition to voice music therapy, there is also the benefit of audio his murotar his Quran as a method of mental health therapy. This study uses descriptive analysis, a literature review technique. Relevant and qualitative discussion of the results of the literature survey in the form of a theoretical explanation. The results and discussion of this study show that the Audio Murotal Qur'an can support therapy and improve mental health. Because the Murotal Qur'an is a poem with good meaning and can have a positive psychological effect. The human voice is an amazing healing tool because the Murotal Qur'an is basically chanted with a human voice. Because sound can reduce stress her hormones, activate natural endorphins, increase relaxation and distract from anxiety, fear and tension. This is evidenced by research conducted by Al-Qadhi in a large clinic located in Florida, United States, which shows that using Audio Murottal Quran helps him reduce depression, stress and mental calmness. You can get good psychological changes with up to 97% effectiveness of. It is felt and the healing of the disease is physiologically supported by the tool.